Kebijakan Pendidikan Merdeka Belajar Kampus Merdeka di Universitas Buana Perjuangan Karawang - Siti Masruroh; Supiana Supiana; Qiqi Yuliati Zaqiah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Merdeka Belajar Kampus education policy aims to prepare students to become resilient scholars, relevant to the needs of the times, and ready to become leaders in the future, namely with innovative, creative and integrative learning systems based on Learning outcomes (LO). Merdeka Belajar-Kampus Merdeka Policy at Buana Perjuangan Karawang University begins with MOU/SPK at the university level, Faculty and Study program with an independent program of independent campus learning is to increase graduate competition both soft skills and hard skills. Mini research method in the form of qualitative methods with data collection through observation and interviews with the mbkm curriculum framer team of Buana Perjuangan Karawang University supported by literature as a support in the collection of mini-research data.